FGF19 and muscle architecture in older patients - Emilie Bres; Julia Bouvier; Aymeric Courtay; Léo Delaire; Joannes Humblot; Charlotte Cuerq; Stéphanie Tripoz-Dit-Masson; Mathieu Fauvernier; Thomas Gilbert; Marc Bonnefoy (Experimental Gerontology, 2023)
Background: Sarcopenia has a significant medical and economic impact. Serum fibroblast growth factor 19 (FGF19) has recently been described as promoting muscle mass and strength, and could be an interesting marker for early diagnosis of sarcopenia and prevention of its consequences. Ultrasound is a robust non-invasive technique used to measure muscle parameters, which cannot be evaluated by usual body composition measures, but are known to be associated with muscle function. In this cross-sectional cohort study, we aimed to determine whether FGF19 levels were correlated with functional muscle tests and muscle ultrasound parameters. Methods: Patients over 70 years old with a mobility disability risk were recruited from the cohort of the “well on your feet” mobility loss prevention program. Sarcopenia was diagnosed according to the European Working Group on Sarcopenia in Older Patients 2 (EWGSOP2) criteria. We have performed functional battery tests, muscle ultrasound measures and bioimpedance spectroscopy. FGF19 levels were measured by the ELISA method. Results: Out of 52 patients involved (34 women, mean age 81.3 years), 30 patients were sarcopenic (15 patients with probable sarcopenia and 15 with certain sarcopenia). Sarcopenic patients were older (mean 82.8 versus 79.6 years, P = 0.033), with higher frailty Fried score (P = 0.006), lower IADL score (P = 0.008), had lower daily protein intakes (P = 0.023) and were less performant to muscle functional tests than non-sarcopenic patients. Serum FGF19 levels were negatively correlated with the SPPB score (rs = 0.28; P = 0.045). FGF19 levels were correlated positively with the pennation angle (rs = 0.31; P = 0.024), but negatively with muscle fiber length (rs = −0.44; P = 0.001). We found no association between FGF19 and muscle thickness (P = 0.243). Conclusion: We highlighted in older patients significant correlations between FGF19 levels, pennation angle and muscle fiber length, suggesting that FGF19 could provide an enabling environment for the development of large muscle fibers, as previously suggested in histological studies in mice. However, high FGF-19 levels were unexpectedly associated with a low SPPB score. Further studies are needed to validate and further elucidate these exploratory findings.